PERAN SUPERVISI PENDIDIKAN DALAM MENINGKATKAN MUTU PENDIDIKAN - Darmayanti, Aprian; Suherman, Suherman (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This study aims to determine the function of educational supervision in improving the quality of education. This study is qualitative and uses case studies. After the data are collected, they are compiled, analyzed, and conclusions are drawn so that conclusions can be drawn after conducting literature research. The results of the study indicate that educational supervision has several functions: a) as a coordinator, he can organize teaching and learning programs and staff member tasks and different activities among teachers; b) as a consultant, he can provide assistance and discuss problems faced by teachers both individually and in groups using his supervision techniques; and c) as a group leader, he can organize activities among teachers simultaneously. d) As an evaluator, he has the ability to help teachers assess learning outcomes and processes, as well as assess the curriculum being prepared. Judging from the meaning and purpose of supervision, it greatly contributes to improving the quality of education. In conclusion, educational supervision helps principals and teachers maximize their potential.